Tear lysozyme levels in contact lens wearers. - (:unkn) unknown (My University, 1991)
Tear lysozyme levels in various types of asymptomatic contact lens wearers were compared with those in age- and sex-matched healthy control subjects. We used a radial immunodiffusion technique, and the lysozyme levels were in the normal range in controls and contact lens wearers. A comparison of the tear lysozyme levels of 27 contact lens wearers (mean, 1.05 +/- 0.45 g/L) with 22 control subjects (mean, 0.84 +/- 0.39 g/L) was statistically significant (P less than .05). The mean tear lysozyme levels of rigid (1.12 +/- 0.54 g/L, P less than .05) and high water-content (1.20 +/- 0.43 g/L, P less than .03) contact lens wearers were increased in comparison with the control group. The tear lysozyme difference was significant (P less than .03) between high and low water-content (0.82 +/- 0.20 g/L) contact lens users. Our study revealed that, although most of the contact lens wearers were asymptomatic and there was no pathologic sign of external ocular inflammation, a change in tear lysozymes was observed. Contact lens wear is irritating to the cornea and conjunctiva, and tear lysozyme physiology is disturbed most by high water-content contact lenses.